ANTI-INFLAMMATORY EFFECT OF METHANOLIC EXTRACT OF LEAVES OF VARIOUS PLANTS - HEMAMALINI. K; DR. ANURAG BHARGAVA (International Journal of Pharma and Bio Sciences, 2013)
The aim of this study is to establish the anti-inflammatory activity by using carrageenan induced paw oedema in rats for methanolic extract of leaves of Solanum pubescens, Sophora interrupta Bedd. and Tabebuia rosea. The effect was assessed by difference in paw oedema volume, before & after the dose administration of the extracts in rats. Anti-inflammatory effects were compared with Standard drug- Indomethacin (10mg./kg/ml.). These observations helped us to conclude that methanolic extract of Solanum pubescens, Sophora interrupta Bedd and Tabebuia rosea is endowed with anti-inflammatory property.